2017
DOI: 10.1590/1678-457x.30816
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo antioxidant activities of polyphenol extracted from black garlic

Abstract: This study investigated the in vitro and in vivo antioxidant activities of polyphenol extracted from black garlic. Black garlic polyphenol (BGP) was extracted from black garlic. The in vitro antioxidant activities of BGP were determined using DPPH·, OH and O 2-radical scavenging assays. The in vivo antioxidant activities were determined by detecting the malondialdehyde (MDA) content and superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) activities in mice. Results showed that, the DPPH· radical inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 23 publications
2
7
1
2
Order By: Relevance
“…In the other study, malondialdehyde content in black garlic groups at 20 and 40 mg / kg animal study doses significantly was reduced (p <0.05). In addition to this, Serum superoxide dismutase activities which are showing the effectiveness of antioxidant system in black garlic groups at 20 and 40 mg / kg animal study doses were significantly higher (p >0.05) [25]. Table 1 antioxidant activity data in this study support this.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…In the other study, malondialdehyde content in black garlic groups at 20 and 40 mg / kg animal study doses significantly was reduced (p <0.05). In addition to this, Serum superoxide dismutase activities which are showing the effectiveness of antioxidant system in black garlic groups at 20 and 40 mg / kg animal study doses were significantly higher (p >0.05) [25]. Table 1 antioxidant activity data in this study support this.…”
Section: Resultssupporting
confidence: 78%
“…In a study the FRAP value in Taşköprü black garlic (640.76±86.98 µmol.g -1 ) slightly decreased from FRAP value of black garlic in Chinese type (678.20±77.56 µmol.g -1 ) [29] but in this study, FRAP value of black garlic (42.16±0.04 µM/mg) was found and this value was quitely high per gram (Table 1). In the other study, The IC50 value of polyphenol extracted from black garlic for DPPH• radical inhibition was 140.79 μg/mL [25] but in this study, the IC50 value of black garlic methanolic extract for DPPH• radical inhibition was found as 180 μg/mL ( Table 1). The reason for this is that the total content of black garlic including flavonoid and sugar groups decreases the antioxidant activity.…”
Section: Resultscontrasting
confidence: 57%
“…Wang and Sun reported that black garlic ethanol extract has an identical DPPH radical inhibitory effect with vitamin C in concentrations 200 and 250 μg/ ml and comparable OH radical scavenging effect with vitamin C in concentrations 400 and 500 μg/ml. Black garlic extract could reduce malondialdehyde (MDA) concentration in serum, an end product of lipid peroxidation, and enhance serum superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) activities in oxidative damage murine model induced by benzene bromide [28]. These results were similar with Lee and collaborators work.…”
Section: Black Garlic and Its Antioxidant Propertiessupporting
confidence: 82%
“…Nillert and collaborators had established a neuronal degenerative model by treatment with 1 μl of aggregated Aβ in the lateral ventricles; eventually they observed that ethanol extract-aged black garlic, a variant form of black garlic produced by aging the fresh garlic in room temperature, could ameliorate short-term recognition memory and inhibit activation of microglia as well as production of IL1β, a proinflammatory cytokine [46]. Additionally, ethyl acetate fraction of aged garlic extract protects PC12 neuron-like cells and ICR mice from neurotoxicity and amnesia induced by Aβ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) [47]. Note that both aged and black garlics are rich of S-allyl-cysteine content, a stable bioactive organosulfur compound which also exerts anti-inflammatory, neuroprotective, and antioxidant effects [48].…”
Section: Neuroprotective Effect Of Black Garlicmentioning
confidence: 99%
“…temperature 70 °C and humidity 80% for 14 days (Choi et al, 2014). Peeled black garlic was dried after fine chopping in a 50 °C oven and then ground to the powder (Wang & Sun, 2017). Black garlic powder was kept chilled until it was added to the duck nugget formulation.…”
Section: Introductionmentioning
confidence: 99%